SELF-PACED READING AND THE ACHIEVEMENT OF PERSIAN EFL LEARNERS - Amir Toghyani Khorasgani (University of Kuningan, 2013)
Abstract: This study aimed at investigating the effects of reading goals on L2 reading comprehension in a computer-mediated environment when reading is self-paced by the learners and students are responsible for their own comprehension. Sixty participants (30 males 30 females) in three groups of 20 were involved. A computer program, written in C#.NET program, presented the text on the screen four lines at a time, and measured the amount of time students would spend on each page initially, how many times students re-read pages, and how much time students would spend re-reading pages. L2 learners’ comprehension and learning strategies were measured in three ways: recall of materials, time spent reading each page of the text and time spent re-reading pages, and the number of times pages were re-read. Finally, after one month from the first test a posttest was administered to determine which group could remember materials better. The results revealed that recall of materials was significantly greater for the teaching-goal group than the other two groups in both first and second tests. Time spent re-reading was significantly greater for the teaching-goal group as well. These findings suggest that reading goals do have an effect on comprehension and recalling in a computer-mediated environment and students with a different reading goal performed differently while reading passages. Keywords: reading goals, computer-mediated reading environment, learning, immediate and delayed recall.